An asphalt binder for a carbon brick lining of a blast furnace and a method for its production

CN122482826BActive Publication Date: 2026-10-13NINGXIA YINHAI HONGXING COAL CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610980999.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-13
Estimated Expiration
2046-07-02

AI Technical Summary

Technical Problem

[0003]但是在实际应用过程中,碳砖配料中电煅无烟煤、石墨等骨料占比达70-80%,添加剂直接加入后容易被骨料吸附,难以均匀分散,形成大量团聚颗粒,不仅无法发挥抗氧化作用,还会成为碳砖的结构缺陷,导致抗热震性下降

Benefits of technology

[0008]本申请的技术效果在于:本申请在制备沥青粘结剂时,用改性后的抗氧化纳米颗粒与沥青混合制备成母粒,再将母粒与沥青分批次混合,进行造粒,将固态沥青粘结剂与碳质骨料混合,用于制备高炉碳砖,与现有的碳砖相比,抗氧化和侵蚀能力更强,不易粉化,使用寿命更长。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a preparation method of pitch binder for blast furnace carbon brick lining, comprising the following steps: heating pitch to 200-240 DEG C, melting the pitch and continuously stirring; adding anti-oxidant master batch in batches, the total addition amount of the anti-oxidant master batch is 3-5 wt% of the mass of the pitch, so that the pitch is uniformly mixed with the anti-oxidant master batch, and a molten mixture is obtained; granulating the molten mixture to obtain solid pitch binder; the anti-oxidant master batch is obtained by the following method: compounding B4C and SiC in a mass ratio of 0.9:1.1 to 1.1:0.9 to obtain nanoparticles with an average particle size of 180-220 nm; wet-modifying the nanoparticles by using a silane coupling agent, the addition amount of the silane coupling agent is 1.8-2.0% of the mass of the nanoparticles, to obtain modified nanoparticles; mixing the dried modified nanoparticles with molten pitch at 140-160 DEG C in a mass ratio of 0.9:1.1 to 1.1:0.9 to obtain the anti-oxidant master batch. Compared with the existing carbon brick, the anti-oxidation and corrosion resistance are stronger, the pitch is not easy to be pulverized, and the service life is longer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of bitumen binders, and more particularly to a bitumen binder for use in the lining of carbon bricks in blast furnaces and a method for preparing the same. Background Technology

[0002] The carbon brick lining of a blast furnace hearth is in long-term contact with molten iron at temperatures above 1500°C and oxidizing slag, making the carbon bricks susceptible to erosion and pulverization by O2 and CO2 in the furnace atmosphere. To improve the erosion resistance of carbon bricks, antioxidants are generally added. For example, Chinese invention patent application number CN202511247517.5, entitled "A Low-Carbon Magnesia-Carbon Brick and Its Preparation Method," describes a low-carbon magnesia-carbon brick characterized by comprising the following components in parts by weight: 80-90 parts of fused magnesia particles, 15-25 parts of fused magnesia fine powder, 5-10 parts of flake graphite, 1-5 parts of nano-carbon powder, 10-20 parts of phenolic resin, 0.2-1.5 parts of curing agent, 0.5-3 parts of antioxidant, and 1-8 parts of modifier. This solution significantly reduces the problems of loose brick structure and spalling caused by oxidation reactions and slag erosion at high temperatures through a gradient skeleton design of fused magnesia particles and fine powder, the construction of a composite carbon network of flake graphite and nano-carbon powder, and a protective layer formed by phenolic resin curing. It enhances the overall stability and damage resistance of the material, enabling the brick to remain dense and strong in complex high-temperature environments.

[0003] However, in practical applications, the proportion of aggregates such as electric calcined anthracite and graphite in carbon brick batches reaches 70-80%. After the additives are added directly, they are easily adsorbed by the aggregates and are difficult to disperse evenly, forming a large number of agglomerated particles. Not only can they not play an antioxidant role, but they will also become structural defects of carbon bricks, leading to a decrease in thermal shock resistance. Summary of the Invention

[0004] In view of this, this application proposes an asphalt binder for blast furnace carbon brick linings, and carbon bricks prepared using this asphalt binder can significantly improve their anti-pulverization performance.

[0005] This application also proposes a method for preparing the aforementioned asphalt binder.

[0006] A method for preparing an asphalt binder for blast furnace carbon brick linings includes the following steps: Heat the asphalt to 200-240℃ to melt it and stir continuously. Antioxidant masterbatch is added in batches, with the total amount of antioxidant masterbatch being 3-5 wt% of the asphalt mass, so that the asphalt and antioxidant masterbatch are mixed evenly to obtain a molten mixture; The molten mixture is granulated to obtain a solid asphalt binder; The antioxidant masterbatch is obtained through the following method: B4C and SiC were compounded in a mass ratio of 0.9:1.1 to 1.1:0.9 to obtain nanoparticles with an average particle size of 180 to 220 nm. The nanoparticles were modified by wet process using a silane coupling agent, with the amount of silane coupling agent added being 1.8–2.0% of the mass of the nanoparticles, to obtain modified nanoparticles. The dried modified nanoparticles were mixed with molten asphalt at 140–160°C in a mass ratio of 0.9:1.1 to 1.1:0.9 to obtain antioxidant masterbatch.

[0007] An asphalt binder for use in the lining of carbon bricks in blast furnaces is prepared by the above method.

[0008] The technical advantages of this application are as follows: In the preparation of asphalt binder, modified antioxidant nanoparticles are mixed with asphalt to prepare masterbatch, and then the masterbatch is mixed with asphalt in batches for granulation. The solid asphalt binder is mixed with carbonaceous aggregate to prepare blast furnace carbon bricks. Compared with existing carbon bricks, it has stronger antioxidant and erosion resistance, is not easy to pulverize, and has a longer service life. Detailed Implementation

[0009] The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0010] A method for preparing an asphalt binder for blast furnace carbon brick linings includes the following steps: The asphalt is heated to 200-240°C to melt it and is continuously stirred; in a preferred embodiment, the asphalt is medium-temperature coal tar pitch.

[0011] At 200–240℃, asphalt can fully melt, thereby uniformly dispersing the asphaltenes, resins, and oil phase components, reducing the interfacial resistance when mixing with antioxidant masterbatch; at the same time, the antioxidant masterbatch can be fully wetted on the asphalt surface and is not prone to agglomeration.

[0012] Antioxidant masterbatch is added in batches, with the total amount of antioxidant masterbatch being 3-5 wt% of the asphalt mass, so that the asphalt and antioxidant masterbatch are mixed evenly to obtain a molten mixture; Adding materials in batches can prevent high-concentration particles from agglomerating in the asphalt viscous system and forming hard agglomerates that are difficult to disperse when a large amount of masterbatch is added at once, which would result in excessively high local particle concentrations and cause fluctuations in the performance of carbon bricks.

[0013] In a preferred embodiment, the antioxidant masterbatch is added in three batches: 40-50% of the total mass is added for the first time, 30-40% of the total mass is added after stirring for 15 minutes, and the remaining antioxidant is added after stirring for another 10 minutes, with a total mixing time of 35-45 minutes.

[0014] The molten mixture is granulated to obtain a solid asphalt binder; The antioxidant masterbatch is obtained through the following method: B4C and SiC were compounded in a mass ratio of 0.9:1.1 to 1.1:0.9 to obtain nanoparticles with an average particle size of 180 to 220 nm. In a preferred embodiment, the preparation process of the nanoparticles is as follows: Micron-sized B4C and SiC powders with a purity ≥99% were selected, mixed in a 1:1 mass ratio, and dried in a vacuum drying oven at 120℃ for 2 hours to remove surface adsorbed water. The mixed powder was fed into a vertical stirred ball mill under inert gas protection. Silicon nitride grinding balls were added at a ball-to-powder ratio of 15:1. Anhydrous ethanol was used as the grinding medium. The grinding speed was 300-400 rpm and the grinding time was 8-10 h to obtain nano slurry. After the slurry is spray-dried, it is classified using a horizontal air classifier. The speed of the classifier wheel is controlled at 12,000 to 15,000 rpm to separate nanoparticles with a particle size of 180 to 220 nm. Unqualified coarse particles are returned to the ball milling process for recycling. After grading, the particles are soaked in 1% dilute hydrochloric acid to remove surface impurities, rinsed with deionized water until neutral, and then dried before being used in the subsequent silane modification process.

[0015] During the preparation of nanoparticles, B4C and SiC can be thoroughly mixed.

[0016] The nanoparticles were modified by wet process using a silane coupling agent, with the preferred amount of silane coupling agent being 1.8–2.0% of the nanoparticle mass, to obtain modified nanoparticles. In a preferred embodiment, the wet modification process is as follows: nanoparticles are dispersed in an aqueous ethanol solution, the pH is adjusted to 8-9 with ammonia, a silane coupling agent is added, and the mixture is ultrasonically stirred at 50-60°C for 30-40 minutes in an ultrasonic reactor. After filtration, the modified nanoparticles are obtained by drying.

[0017] This application utilizes wet modification to enhance the bonding ability between nanoparticles and asphalt. Ultrasonic stirring aims to fully modify the surface of the nanoparticles. The activation index of the nanoparticles reflects the modification effect.

[0018] Before modification, the surface of B4C / SiC nanoparticles is hydrophilic and will naturally sink and disperse when placed in water. After modification with silane coupling agent, organic hydrophobic segments are grafted onto the surface of the particles, which become oleophilic. When placed in water, they will float on the surface of the water without being wetted due to the hydrophobic effect.

[0019] Activation index = (mass of particles floating on the water surface ÷ total mass of added particles) × 100%; a higher activation index indicates more complete modification. The preferred activation index in this application is above 90%. Experiments showed that the activation index of the nanoparticles could reach 90% after ultrasonic stirring at 50–60°C for approximately 30 minutes. Furthermore, as the ultrasonic stirring time increased, the increase in activation index significantly decreased around 40 minutes. Therefore, the ultrasonic stirring time in this application is 30–40 minutes.

[0020] To prevent excessively high system temperature during ultrasonic stirring, in a preferred embodiment, this application employs a stirring vessel with a cooling jacket, controlling the system temperature through circulating cooling water within the jacket. Simultaneously, this application also employs pulsed ultrasonic stirring, for example, a periodic working mode of 5 seconds followed by a 3-second interval, with a processing time of 30–40 minutes, to prevent continuous temperature rise in the system through intermittent stirring. Furthermore, to prevent excessive ultrasonic energy from damaging the covalent bonds on the modified nanoparticles, this application uses an ultrasonic power of 30–50 W / L. By using low power and pulsed ultrasonic stirring, the heat generated during ultrasonic stirring can be effectively reduced, while avoiding high energy damage to the covalent bonds on the modified nanoparticles.

[0021] The dried modified nanoparticles are mixed with molten asphalt at 140–160°C in a mass ratio of 0.9:1.1 to 1.1:0.9 to obtain antioxidant masterbatch. In a preferred embodiment, the asphalt used for the antioxidant masterbatch is low-temperature coal tar pitch.

[0022] B4C and SiC are nanoparticles with large specific surface areas and high surface energy. When directly added to molten asphalt at temperatures above 200°C, they agglomerate: upon contact with the high-temperature asphalt, the air adsorbed on the surface expands to form an air film, preventing the asphalt from wetting the particles. This causes a large number of nanoparticles to agglomerate into micron-sized hard clusters that are difficult to break even under subsequent long-term shearing. In this application, the nanoparticles are first blended with asphalt under mild conditions of 140–160°C, and the nanoparticles are also modified to enhance their bonding ability with asphalt.

[0023] After nanoparticles and asphalt form a masterbatch, the modified nanoparticles form chemical bonds with the asphalt. When then added to the molten main asphalt, the asphalt in the masterbatch carries the nanoparticles and dissolves into the main asphalt without generating new agglomerates. Therefore, the nanoparticles of this application exhibit excellent dispersibility in asphalt.

[0024] The asphalt binder prepared in this application is in the form of solid particles, which facilitates storage and transportation. Furthermore, compared to liquid asphalt, the nanoparticles are less prone to separation from the asphalt and maintain good dispersibility even after long-term storage.

[0025] In a preferred embodiment, during the preparation of carbon bricks, the asphalt binder prepared in this application is first premixed with carbon powder at a low temperature, and then heated to above 160°C to ensure thorough mixing and molding of the asphalt binder and carbon powder. The asphalt binder forms a spatial network structure in the carbon powder, with nanoparticles uniformly distributed on the network structure. The mixture is then pressed into carbon blanks, which serve as the prototype for the blast furnace carbon brick lining. After the blast furnace is heated, the carbon blanks are fired into carbon bricks. During firing, B4C and SiC react with oxygen in the carbon bricks to generate corresponding oxides. Simultaneously, the high temperature fires these oxides into a glassy phase. During firing, the long-chain structure formed by asphalt carbonization, combined with the oxides in the glassy phase, effectively locks the carbon powder in place, effectively slowing down carbon brick pulverization and inhibiting carbon powder oxidation, thus significantly improving the service life of the carbon bricks.

[0026] In a preferred embodiment, the granulation process is as follows: The constant-temperature asphalt liquid is fed into the pelletizer die head at a pressure of 0.3-0.5MPa using a screw pump. The die head diameter is selected from 2.5 to 4mm according to the requirements. The die head temperature is maintained at 200-220℃ to prevent asphalt from condensing and clogging the die head. Asphalt is extruded from the die and immediately cut into uniform cylindrical segments by a high-speed rotating cutter. The cutter speed is adjusted according to the target particle size: 200-300 r / min when producing 2-3 mm particles, and 120-180 r / min when producing 3-5 mm particles. After being cut, the material segments enter the circulating cooling water chamber, where the water temperature is at room temperature, so that the asphalt material segments can be cooled and shaped quickly to avoid particle deformation and adhesion. The discharged particles first enter a centrifugal dehydrator to remove surface free water at a speed of 1000-1500 r / min, and then are dried with hot air to prevent clumping during subsequent storage.

[0027] An asphalt binder for use in the lining of carbon bricks in blast furnaces is prepared by the above method.

[0028] The effectiveness of this solution will be verified through examples and comparative examples below. All samples were prepared using the same carbon brick process: 65wt% carbonaceous aggregate (1-5mm calcined coke), 35wt% graphite powder preheated to 180℃, asphalt binder added at 17wt% of aggregate mass, kneaded for 40min, molded at 30MPa, and calcined at 1350℃ for 25h before performance testing.

[0029] Test conditions Temperature: 1200℃, simulating the actual working temperature of a blast furnace.

[0030] Atmosphere: Air + 20 vol% CO2 + 5 vol% K2CO3 vapor, simulating an oxidizing and highly alkaline environment.

[0031] Cyclic regime: Each cycle is 12 hours. After holding at 1200℃ for 11 hours, the furnace is taken out and directly air-cooled to room temperature for 1 hour to simulate the thermal shock of blast furnace shutdown / restart.

[0032] Total test duration: 10 cycles, totaling 120 hours.

[0033] Evaluation indicators: thickness of the powdery layer on the surface of the sample after the test, and the powdery layer shedding rate.

[0034] The thickness of the powdery layer on the sample surface was measured using the following method: a standard steel wire scraper with a hardness of HRC55 was used to scrape the sample surface under constant pressure. The loose layer that can be easily scraped off is the completely powdered layer. Stop scraping when the resistance increases significantly and the scraped debris changes from powder to granular particles. The thickness difference of the sample before and after scraping is measured with vernier calipers, which is the thickness of the powdered layer. The average value is taken from 5 parallel measurements.

[0035] The powder layer shedding rate was monitored in the following way: the sample surface was gently brushed with a soft brush, and the proportion of the mass of the powder layer that detached to the total mass of the sample was the powder layer shedding rate.

[0036] Example 1 Prepare asphalt binder according to the following parameters: Preparation of antioxidant masterbatch: B4C to SiC mass ratio 1:1, average particle size of nanoparticles 200nm; silane coupling agent KH550 added at 1.9% of the mass of nanoparticles, after wet modification, mixed with asphalt at a mass ratio of 1:1 at 150℃ and 400rpm for 25min, cooled and crushed into 0.5-2mm masterbatch; The main asphalt is heated to 220℃ to melt; The masterbatch was added to the base asphalt in three batches, with a total addition amount of 4 wt% of the base asphalt mass and a total mixing time of 40 min. Underwater pelletizing at a water temperature of 25℃ yields asphalt binder with a particle size of 2–5 mm.

[0037] Example 2 This embodiment adjusts the masterbatch addition ratio and B4C / SiC ratio to suit the high erosion conditions of the blast furnace hearth sidewall: Preparation of antioxidant masterbatch: B4C to SiC mass ratio 1.1:0.9, average particle size of nanoparticles 210nm; KH550 addition amount is 2.0% of the mass of nanoparticles, and mixed with low softening point asphalt at 1.1:0.9 mass ratio at 160℃ and 500rpm for 20min. The main asphalt is heated to 230℃ to melt; The masterbatch was added to the base asphalt in three batches, with a total addition amount of 5 wt% of the base asphalt mass. The finished product is obtained by underwater pelletizing.

[0038] Comparative Example 1 Ordinary medium-temperature asphalt without any added antioxidants was used as the binder, and the rest of the carbon brick preparation process was the same as in the example.

[0039] Comparative Example 2 Unmodified B4C / SiC nanoparticles of the same amount were directly added to molten asphalt and mixed. The total amount added was 2 wt% of the asphalt mass, and the ratio of B4C to SiC was 1:1. The rest of the process was the same as in Example 1.

[0040] Comparative Example 3 The same amount of B4C / SiC nanoparticles were directly mixed with carbonaceous aggregate, and ordinary asphalt was used as the binder. The rest of the process was the same as in Example 1.

[0041] Comparative Example 4 In the preparation of antioxidant masterbatch, the nanoparticles are not modified by silane coupling agent, but are directly mixed with low softening point asphalt to prepare masterbatch, and the rest of the process is the same as in Example 1.

[0042] Comparative Example 5 The total amount of antioxidant masterbatch added was 1 wt% of the asphalt mass, and the rest of the process was the same as in Example 1.

[0043] Comparative Example 6 The total amount of antioxidant masterbatch added was 8 wt% of the asphalt mass, and the rest of the process was the same as in Example 1.

[0044] The results of the above experiments are shown in Table 1.

[0045] Table 1 Compared with Comparative Example 1, the thickness of the pulverized layer in Comparative Example 1 was 18.2 mm, while the thickness of the pulverized layer in Example 1 was 0.8 mm. The pulverized layer peeling rate was 12.7% in Comparative Example 1 and 0.32% in Example 1. No anti-oxidation measures were taken in Comparative Example 1. Therefore, it can be seen that antioxidants can significantly improve the pulverization resistance of carbon bricks.

[0046] Compared with Comparative Example 2, the thickness of the powdery layer in Example 1 was 8.7 mm in Comparative Example 2 and 0.8 mm in Example 1; the powdery layer peeling rate was 5.1% in Comparative Example 2 and 0.32% in Example 1. Comparative Example 2 incorporated the same amount of unmodified nanoparticles into asphalt. Therefore, it can be seen that the modified antioxidant significantly improves the anti-powdering effect of carbon bricks compared to the unmodified antioxidant.

[0047] Compared with Comparative Example 3, the thickness of the pulverized layer in Example 1 was 10.3 mm in Comparative Example 3 and 0.8 mm in Example 1; the pulverized layer shedding rate was 6.4% in Comparative Example 3 and 0.32% in Example 1. In Comparative Example 3, the same amount of antioxidant was directly mixed with carbonaceous aggregate without being loaded into the asphalt matrix. This demonstrates that mixing asphalt binder with antioxidants and carbonaceous aggregate can significantly improve the pulverization resistance of carbon bricks.

[0048] Compared with Comparative Example 4, the thickness of the powdered layer in Example 1 was 0.8 mm, while that in Comparative Example 4 was 5.2 mm. The powdered layer shedding rate was 2.8% in Comparative Example 4 and 0.32% in Example 1. The B4C / SiC particles in Comparative Example 4 were not modified with a silane coupling agent; the masterbatch was prepared solely through physical mixing. This demonstrates that silane modification achieves chemical bond anchoring between the nanoparticles and the asphalt, preventing particle detachment from the interface during asphalt carbonization and thermal shock cycling, and significantly improving the bonding reliability between the antioxidant glassy phase layer and the carbon matrix.

[0049] Compared with Comparative Example 5, the thickness of the pulverized layer in Example 1 was 0.8 mm, while that in Comparative Example 5 was 4.8 mm. The pulverized layer shedding rate was 2.6% in Comparative Example 5 and 0.32% in Example 1. The amount of masterbatch added in Comparative Example 5 was only 1 wt%, lower than the optimal range of 3-5 wt% in this application. This indicates that when the antioxidant content is too low, the pores of the carbon brick cannot be completely sealed, and oxygen and alkaline vapors can still penetrate the internal carbon dioxide matrix, leading to a significant decrease in anti-pulverization performance.

[0050] Compared with Comparative Example 6, the thickness of the powdery layer in Example 1 was 0.7 mm, which was basically the same as the 0.8 mm in Example 1; the powdery layer peeling rate was 1.2% in Comparative Example 6, which was 3.75 times that of Example 1. This shows that adding excessive antioxidants not only does not further improve the anti-powdering performance, but also damages the bonding network structure of asphalt, leading to a decrease in the mechanical strength of carbon bricks, a reduction in the bonding force between the powdery layer and the matrix, and making it more prone to peeling.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A method for preparing an asphalt binder for blast furnace carbon brick linings, characterized in that, Includes the following steps: Heat the asphalt to 200-240℃ to melt it and stir continuously. Antioxidant masterbatch is added in batches, with the total amount of antioxidant masterbatch being 3-5 wt% of the asphalt mass, so that the asphalt and antioxidant masterbatch are mixed evenly to obtain a molten mixture; The molten mixture is granulated to obtain a solid asphalt binder; The antioxidant masterbatch is obtained through the following method: B4C and SiC were compounded in a mass ratio of 0.9:1.1 to 1.1:0.9 to obtain nanoparticles with an average particle size of 180 to 220 nm. The nanoparticles were modified by wet process using a silane coupling agent, with the amount of silane coupling agent added being 1.8–2.0% of the mass of the nanoparticles, to obtain modified nanoparticles. The dried modified nanoparticles were mixed with molten asphalt at 140–160°C in a mass ratio of 0.9:1.1 to 1.1:0.9 to obtain antioxidant masterbatch.

2. The method for preparing the asphalt binder for blast furnace carbon brick lining as described in claim 1, characterized in that, The antioxidant masterbatch is added in three batches: 40-50% of the total mass is added first, followed by 30-40% of the total mass after stirring for 15 minutes, and the remaining antioxidant is added after stirring for another 10 minutes. The total mixing time is 35-45 minutes.

3. The method for preparing the asphalt binder for blast furnace carbon brick lining as described in claim 1, characterized in that, The nanoparticles were modified by wet process using a silane coupling agent. Specifically, the nanoparticles were dispersed in an ethanol aqueous solution, the pH was adjusted to 8-9 with ammonia, a silane coupling agent was added, and the mixture was ultrasonically stirred at 50-60℃ for 30-40 min. After filtration, the nanoparticles were dried to obtain the modified nanoparticles.

4. The method for preparing the asphalt binder for blast furnace carbon brick lining as described in claim 1, characterized in that, The silane coupling agent is KH550 silane coupling agent.

5. The method for preparing the asphalt binder for blast furnace carbon brick lining as described in claim 1, characterized in that, The particle size of the antioxidant masterbatch is 0.5–2 mm.

6. The method for preparing the asphalt binder for blast furnace carbon brick lining as described in claim 1, characterized in that, The underwater pelletizing process is used, with a pelletizing water temperature of 20-30℃, resulting in a finished asphalt binder with a particle size of 2-5mm.

7. An asphalt binder for use in the lining of carbon bricks in blast furnaces, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Low-carbon magnesium carbon brick and preparation method thereof

    CN120736882B

  • Low carbon ultra-low carbon magnesium-calcium-carbon refractory material for lining in steelmaking refining furnace and preparation method of low carbon ultra-low carbon magnesium-calcium-carbon refractory material

    CN110330314A

  • Low-aluminum refined ladle brick and preparation method thereof

    CN120398516A